How to Increase Machine Efficiency in the Diaper Production Process Using a Lean Manufacturing Approach - Hibarkah Kurnia; Adriana Anteng Anggorowati; Arif Nuryono; Nur Ain Jaelani (Widya Teknik, 2026)
In today's manufacturing world, competition is increasingly fierce; therefore, every company is trying its best to increase productivity as one of the strategies to be able to compete in the market. PT. XYZ is currently facing problems related to the effectiveness of machine or equipment operations. The problem currently being faced is the length of the diaper change production process, which takes up to 8100 seconds/135 minutes, causing a decrease in machine efficiency by 25%. This study aims to reduce the time of the diaper change production process, which takes a long time. The research method employs the Lean Manufacturing (LM) approach, utilising Value Stream Mapping (VSM) and Single Minute Exchange of Dies (SMED) methods to reduce the production time of diaper item changes, thereby increasing machine efficiency. The results of this study showed a diaper change production process time of 135 minutes, and the time after using LM was reduced to 105 minutes. By presenting a diaper change production process time efficiency of 20%, these results indicate that the VSM and SMED methods can be used to reduce waste and speed up the diaper change production process time.